2008
DOI: 10.1007/s11104-008-9563-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of arbuscular mycorrhizal plants originating from xerothermic grasslands on heavy metal rich industrial wastes–new solution for waste revegetation

Abstract: Industrial waste substrata, rich in heavy metals, are poorly suited for plant growth. Efforts are made to establish an appropriate plant cover to reduce erosion and further contamination. Grasses are the usual solution, as they grow fast, thrive on poor substrata and have well-developed root systems. Some of them are also highly dependent on mycorrhizal symbiosis that supports their growth especially on poor and polluted soils. However, the commercially available grasses often meet a lack of well established m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 21 publications
1
30
0
1
Order By: Relevance
“…ischaemum (Shah et al 2009a, Wilson et al 2012, B. pinnatum (van der Heijden et al 1998, Endresz et al 2005, B. inermis (Turnau et al 2008, Shah et al 2009a, C. epigeijos (Rydlová andVosátka 2001, van der Staaij et al 2001) and C. dactylon (Cabello 1997, Lingfei et al 2005). …”
Section: H2)unclassified
“…ischaemum (Shah et al 2009a, Wilson et al 2012, B. pinnatum (van der Heijden et al 1998, Endresz et al 2005, B. inermis (Turnau et al 2008, Shah et al 2009a, C. epigeijos (Rydlová andVosátka 2001, van der Staaij et al 2001) and C. dactylon (Cabello 1997, Lingfei et al 2005). …”
Section: H2)unclassified
“…by Dzwonko andLoster (1998) andBąba (2004). In the present study, seeds of the following plant species were collected: sulcata) studied in the present paper were not investigated in our previous research (Turnau et al 2008) because they were introduced into the tailings later. Moreover, several species that were included in previous studies were omitted here due to poor growth at the time of sampling.…”
Section: Introductionmentioning
confidence: 97%
“…Our previous research on plants and their symbiotic associations occurring spontaneously on the Zn-Pb waste in Chrzanów revealed that the most successful colonizers of such sites are species which originate from xerothermic grasslands (reviewed by Turnau et al 2006). In 2004, 23 plant species, pre-cultivated in the presence of mycorrhizal inoculum, were introduced on experimental plots (Turnau et al 2008). The introduced plants survived and to the naked eye, they did not differ much from individuals growing in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…What is interesting, in contrast with very contaminated substrates such as mine tailings [12][13][14], is that the response of oxidative stress variables for plants grown in unpolluted or slightly polluted soils presents similar patterns of variation in almost all plant parts. However, plants benefit from the effect of mycorrhizal fungi even in such substrates because the fungi enhance drought resistance in them [17,54]. Also, Clemens [7] states that HM stress up-regulates SOD and POD, but that high metal concentrations in plants can also lower the activity of these enzymes either through binding and direct inactivation, or through glutathione consumption.…”
Section: Resultsmentioning
confidence: 99%